Symposium 9: Integrating Digital Resources into Online Learning Environments to Support the Learner - Markland, Margaret; Kemp, Bob (Proceedings of the International Conference on Networked Learning, 2004)
This paper describes an investigation into the ways in which tutors and students identify and obtain online resources and examines some new tools and services which are being developed to enable tutors to integrate the information resources which support their teaching into online learning environments in more efficient ways than are currently possible. Such resources might be found for example, in digital libraries, on university library websites, in electronic journals or books, in reading lists, on the Internet, in existing VLEs, or indeed in any kind of paper-based resource. They could be text, images, speech or music. Current needs and difficulties are explored from the tutor and student perspectives, and what the tools are aiming to provide to help with these issues is described. The paper concludes by suggesting why the need for such tools will be come more urgent as the Government’s initiatives to push teaching and learning out into work and community contexts gathers pace.